An analysis of Malaysia’s regional energy diplomacy: Experience and outcome - Awang Dzul-Hashriq Dharfizi, Awang Salleh (2022)
This research examines Malaysia’s involvement in activities which render energy as the subject and/or object of foreign policies, either via bilateral or multilateral engagements, from the perspective of Neoliberal Institutionalism. Malaysia’s increased involvement in the global energy market necessitates this research which seeks (a) to determine the significance of energy in Malaysia’s economy and diplomacy; (b) to understand Malaysia's motivation for its involvement in these cooperations and (c) to identify steps to enhance its energy security through refinements of existing policies and recognizing new opportunities. This study utilizes information from official sources, interviews, published statistical data and past studies. The findings demonstrate that energy contributes significantly to Malaysia’s economy. Using the Herfindahl-Hirschman Index and the Export Dependency Index, it was discovered that Malaysia is more dependent on its Liquified Natural Gas (LNG) exports to Japan and South Korea than the other way around, and that trades of energy commodities are based on practical consideration. Petronas also acts as an agent for Malaysia’s energy diplomacy in some capacity. In a non-trade arrangement such as the ASEAN Power Grid (APG), Malaysia utilizes ASEAN as a platform to engage with other countries, although this is less evident in the Malaysia- Thailand Joint Development Area (MT-JDA). Through the Malaysia-Thailand Joint Authority (MTJA), both Malaysia and Thailand agree to set-aside their disputes over maritime delimitation to enable joint exploration. Malaysia’s involvement in the Laos-Thailand- Malaysia-Singapore Power Integration Project (LTMS-PIP) initiative demonstrates the viability of multilateral electricity trade in the region. The Four Fuel Diversification Policy 1981 (4FDP 1981) which increases natural gas utilization and the construction of the Peninsular Gas Utilisation (PGU) pipeline are related to Malaysia’s involvement in MT-JDA, whereas the reform of its electricity sector through Malaysia Electricity Supply Industry 2.0 (MESI 2.0) was catalysed through its participation in the APG. While these initiatives contribute towards enhancing Malaysia’s energy security, Malaysia can still play a proactive role in regional energy cooperation by serving as a regional energy hub or transit state. Malaysia may also consider consolidating its energy administration in order to improve efficiency. The experience in negotiating for Joint Development Area (JDA) is useful in addressing the present South China Sea dispute.